Development of an enhanced wide-band erbium doped fiber amplifier using high concentration active medium - Hamida, Belal Ahmed G. Allah (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
In the point-to-point transmission an optical signal suffers mainly from attenuation and dispersion. The ongoing research has been focusing on containing this issue by proposing innovative designs in order to provide for an element compensating these effects. This research work focuses on the development of a new design of wide band high concentration optical amplifier. It suggests compensating for attenuation and dispersion both using the same technique. It consists of two stages of 1.5m and 9m long Erbium-Doped Fiber (EDF) optimized to operate in C-band and L-band, respectively. Further, a Chirped Fiber Bragg grating (CFBG) is used in each section to reflect the amplified signal back to the active area so that the overall gain spectrum can be enhanced over a wider frequency spectrum. Using a semi-analytical model (GainMaster), is suggested to verify the proposed design. A numerical model is carried out to implement the energy rate equations for the erbium ions population inversions. In addition, an extensive work has been carried out to implement this design experimentally. The experimental results show that the proposed amplifier gives a wider (1540nm to 1610m) flat high gain (22dB) with variation of ±3dB and low noise figure less than (6.5dB) at low input signal power (-30dBm) . Though solved by CFBG partially, this work has not carried out a quantified exploration of issues related to dispersion, mainly due to unavailability properly characterized equipment. Also an extensive work has been carried out to evaluate the performance of the proposed amplifier by comparing the performance against other available amplifiers. The performance shows that the band width 5nm higher than the existing amplifier with low noise figure about 7dB and gain flatness about 70nm which is higher than the other two amplifiers by 30dm.